Microbiology in burns patients with blood stream infections: trends over time and during the course of hospitalization. Issue 4 (3rd April 2018) - Sousa, Dolores; Ceniceros, Alejandra; Galeiras, Rita; Pértega-Díaz, Sonia; Gutiérrez-Urbón, José-María; Rodríguez-Mayo, María; López-Suso, Eugenia; Mourelo-Fariña, Mónica; Llinares, Pedro
Abstract: Background: Bloodstream infections (BSI) are a major cause of mortality in burns patients. Knowledge of the microbiology is crucial to direct empirical therapy. We sought to determine the causative microorganisms and antibiotic resistance in burns patients with BSI. Methods: All consecutive BSI episodes in a tertiary hospital burns unit from 2000 to 2014 were included. The following three subperiods were compared: 2000–2004, 2005–2009 and 2010–2014. Changes in BSI occurring during early and late hospitalization periods were evaluated. Results: A total of 103 BSI episodes were included. The cumulative incidence was 2.4 episodes/1000 patient days. A positive trend in the frequency of Gram-negative BSI, especially in the upsurge of Pseudomonas aeruginosa and Klebsiella spp. BSI after 2004, was observed. The most common causative pathogens in early BSI were Gram-positive microorganisms. P. aeruginosa and Klebsiella spp. became the predominant aetiology in the fourth week of hospitalization and beyond. There was a progressive increase in imipenem-resistant P. aeruginosa over time (0%, 67%, 75% in 2000–2004, 2005–2009, 2010–2014, respectively) and during the hospital stay (50% vs. 85.7%, in <7 days-BSI vs. >30 days-BSI, respectively). A higher SOFA (Sepsis-related Organ Failure Assessment) score was associated with Gram-negative BSI versus non-Gram-negative BSI (median: 2.5 vs. 0; p = 0.041). Conclusions: There is a changing trend in the types of pathogens causing BSI in burns patients over the 14-year period and during the course of hospitalization. The problematic increase in carbapenem-resistance highlights the need for new antimicrobial stewardship policies and antibiotic prescribing protocols.